2022
DOI: 10.3389/fnbeh.2022.828599
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism and Clinical Application of Constraint-Induced Movement Therapy in Stroke Rehabilitation

Abstract: Constraint-induced movement therapy (CIMT) has been widely applied in stroke rehabilitation, and most relevant studies have shown that CIMT helps improve patients’ motor function. In practice, however, principal issues include inconsistent immobilization durations and methods, while incidental issues include a narrow application scope and an emotional impact. Although many studies have explored the possible internal mechanisms of CIMT, a mainstream understanding has not been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 65 publications
0
12
0
1
Order By: Relevance
“…CI therapy, also known as CIMT, is a neurorehabilitation therapy aimed at recuperating the function of an affected limb after stroke. The affected limb is forced to be used instead of the healthy one ( Wang et al, 2022 ). Many studies have confirmed the efficacy of CIMT in improving limb motor function ( Ju and Yoon, 2018 ; Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CI therapy, also known as CIMT, is a neurorehabilitation therapy aimed at recuperating the function of an affected limb after stroke. The affected limb is forced to be used instead of the healthy one ( Wang et al, 2022 ). Many studies have confirmed the efficacy of CIMT in improving limb motor function ( Ju and Yoon, 2018 ; Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The affected limb is forced to be used instead of the healthy one ( Wang et al, 2022 ). Many studies have confirmed the efficacy of CIMT in improving limb motor function ( Ju and Yoon, 2018 ; Wang et al, 2022 ). Electroacupuncture therapy combines traditional Chinese medicine acupuncture therapy and Western medicine rehabilitation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The studies included in this meta-analysis used different CIMT protocol and outcome measures, which may bias of CIMT efficacy assessment. A review ( 64 ) mentioned that differences in the types of restrictions, duration of restriction, intervention time, training intensity, and evaluation methods weaken the evidence for the clinical value of CIMT. First, included studies differed in CIMT intensity (ranging from 30 min to 6 h per day) and duration (ranging from 2 weeks to 3 months) because our inclusion criteria did not limit these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…One current therapy is known as constraint-induced movement therapy (CIMT), a neurorehabilitative method where the non-paretic limb is immobilized to promote the use of the weakened limb, thus reducing learned non-use. CIMT has been shown to be beneficial in both human and rodent studies [ 2 ]. The constraint of upper-extremity function between 3 and 9 months post stroke and traumatic brain injury (TBI) was shown to improve recovery, with CIMT patients showing improved function compared to patients who did not receive CIMT [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%